2014
DOI: 10.1111/codi.12490
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with corticosteroids and the risk of anastomotic leakage following lower gastrointestinal surgery: a literature survey

Abstract: Caution should be shown in patients scheduled for lower gastrointestinal surgery with anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 26 publications
(101 reference statements)
1
42
0
Order By: Relevance
“…Prolonged use of corticosteroids may be a risk factor for AL, particularly when combined with other immunosuppressants or in cushingoid patients. A systematic review found an AL rate of 6·8 per cent in the corticosteroid group compared with 3·3 per cent in patients not treated with corticosteroid, but the duration and dose of treatment were heterogeneous. Infliximab alone may not alter AL risk, but in combination with other immune modulators can slow healing.…”
Section: Preoperative Risk Factorsmentioning
confidence: 99%
“…Prolonged use of corticosteroids may be a risk factor for AL, particularly when combined with other immunosuppressants or in cushingoid patients. A systematic review found an AL rate of 6·8 per cent in the corticosteroid group compared with 3·3 per cent in patients not treated with corticosteroid, but the duration and dose of treatment were heterogeneous. Infliximab alone may not alter AL risk, but in combination with other immune modulators can slow healing.…”
Section: Preoperative Risk Factorsmentioning
confidence: 99%
“…Prolonged use of corticosteroids can be a risk factor for AL, particularly when combined with other immunosuppressive drugs [4850] . A recent systematic review reported that the AL rate after lower gastrointestinal surgery was 6.8% in the corticosteroid group compared with 3.3% in the noncorticosteroid group, although the duration and dose of corticosteroid treatment were heterogeneous [51] . A metaanalysis with six RCTs reported that perioperative use of nonsteroidal anti inflammatory drugs (NSAIDs) had no statistically significant effect on the AL rate [52] .…”
Section: Medicationsmentioning
confidence: 99%
“…The AL rate has been variably stated to be between 1% and 19% . A wide variety of factors has been suggested to contribute to the development of AL but there is no clear consensus in the literature . Many of the studies involve small numbers of patients and studies considering the impact of a limited number of factors on the AL rate risk overlooking confounding factors.…”
Section: Introductionmentioning
confidence: 99%